Effect of hydrofluoric acid concentration and etching time on microtensile bond strength of suprinity and enamic CAD/CAM ceramics to resin cement - Fatemeh Yazarloo; Homayoun Alaghehmand; Faraneh Mokhtarpour (Babol University of Medical Sciences, 2019)
Introduction: The use of dental ceramics has increased due to their beauty and biocompatibility. The aim of this study was to evaluate the effect of hydrofluoric acid concentration and etching time on microtensile bond strength (μTBS) of the Enamic and Suprinity ceramics. Material & Methods: In this in vitro study, two hydrofluoric acid (HFA) concentrations of 5% (A) and 10% (B) were used at the time of 20, 60 and 120 seconds (s) on the Suprinity and  Enamic ceramics of CAD/CAM. The etched surfaces were impregnated with silane coupling agent as well as priming and Clearfil SE bond. Then, the Panavia F 2.0  resin cement was applied on the ceramic surfaces and light-cured. There were groups of EA20, EA60, EA120, EB20, EB60, EB120 for Vita Enamic and SA20, SA60, SA120, SB20, SB60, SB120 for Vita Suprinity. The μTBS between resin cement and porcelains was measured with universal testing machine. Mode of failure was observed under the stereo microscope at 40x magnification. Data were analyzed using ANOVA and Chi-square. Results: The μTBS was significantly different between EB20 and EB60 (p=0.008), EB120 and EB20 (p=0.005), SA120 and SB120 (p=0.013), EA120 and EB120 (p=0.002) as well as EA60 and EB60 (p=0.44). In both ceramics, different concentrations and etching times had significant effect on the mean of μTBS (p=0.016). In both ceramics, the time had no effect on the failure mode. For Suprinity ceramic, the HFA concentration had effect on the failure mode (P=0.028). Conclusion: The best surface treatment for Suprinity ceramic is 120 s with 5% HFA and for Enamic is 20 s with 10% HFA, which create the highest bond strength.